Use of polymeric fibers to increase gas permeability of lanthanum carbide based targets for nuclear physics applications. Issue 15 (15th November 2016) - Corradetti, S.; Biasetto, L.; Innocentini, M.D.M.; Carturan, S.; Colombo, P.; Andrighetto, A.
Abstract: Porous lanthanum carbide disks were prepared from La2 O3 and graphite powders and with additions of polymeric fibers as sacrificial templates for the formation of interconnected channels of enhanced permeability to gas flow. Two kind of fibers were used (Nylon 6, 6 and polypropylene) characterized by an average length of 500 µm and diameters of 18 and 20 µm, respectively. The fiber content was varied up to 21.3 vol% for nylon or up to 24.8 vol% for PP in order to control the porosity and the permeability level of bodies. The fiber-derived porous LaCx samples exhibited higher total porosity (38.0–51.7% for PP and 42.9–55.3% for nylon) compared to standard LaCx where porosity (35.7%) was generated only by the carbothermal reaction during sintering. A 50-fold increase in the Darcian permeability coefficient k1 and a 1200-fold increase in the non-Darcian coefficient k2 were achieved in comparison with the permeability level of the composition without fibers (k1 =1.21×10 −15  m 2 and k2 =1.17×10 −11  m). Nylon was slightly better than PP to enhance permeability of LaCx targets.